2017
DOI: 10.1039/c7ra01946g
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of mesoporous graphene platelets with in situ nitrogen and sulfur doping for lithium–sulfur batteries

Abstract: The interaction between lithium polysulfides and doped heteroatoms could prevent the loss of soluble polysulfides in the cathode and mitigate the shuttle effect in lithium-sulfur batteries. Herein, a facile synthesis of mesoporous graphene platelets (NSGs) with in situ nitrogen and sulfur doping by the pyrolysis of a self-assembled L-cysteine precursor on sodium chloride crystal surface for structuredirecting is presented. The mesoporous lamellar structure of the NSG possesses a uniform distribution of pyrroli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…The N1s spectrum (Figure c) contains 4 contributions at 398.2 eV, 400 eV, 401.7 eV and 403.7 eV which are assigned to the pyridinic, pyrrolic, graphitic and nitrogen oxide respectively, which includes 27 at. % pyridinic nitrogen, 34 at.% pyrrolic nitrogen, 25 at.% graphitic nitrogen and 14 at.% N−O species ,. These functional groups are consistent with the FTIR spectral results.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The N1s spectrum (Figure c) contains 4 contributions at 398.2 eV, 400 eV, 401.7 eV and 403.7 eV which are assigned to the pyridinic, pyrrolic, graphitic and nitrogen oxide respectively, which includes 27 at. % pyridinic nitrogen, 34 at.% pyrrolic nitrogen, 25 at.% graphitic nitrogen and 14 at.% N−O species ,. These functional groups are consistent with the FTIR spectral results.…”
Section: Resultssupporting
confidence: 90%
“…The nitrogen (2.22%) and oxygen (14.67%) content obtained from XPS analysis (Table S2) are very close to the CHNS results. The high resolution C1s (Figure a) peak divided into 5 components, C−C bond (284.7 eV) of SP 2 , C−N (285.4), C−O bond (286.6 eV), C=N bond (287.3 eV) and C=O (288.6 eV) . The high resolution O1s spectrum (Figure b) is subdivided into three components: N−O bond (530.5), C−O bond (531.7 eV), and C=O bond (533.1 eV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To adjust the physical and chemical characteristics of carbon materials and thereby to enhance the electrochemical performance of S/C composites, heteroatoms, including boron, nitrogen, oxygen, phosphorus, and sulfur, are often doped into the carbon hosts, especially graphene. By XPS, Guo et al found that the surface of carbon was positively polarized by doping with boron and showed the strong chemisorption ability of sulfur species.…”
Section: Carbon‐based Materialsmentioning
confidence: 99%